Use of polimerase chain reaction for sexing south american camelids - Montenegro V., Vanya (2012)
The objective of this study was to develop a PCR technique to determine the sex of South American camelids (CSA) using Zinc Finger Protein (ZF) sequences from blood and fecal samples, as well as cells from alpaca embryos. A total of 28 alpaca, llama and vicuña blood samples, 20 vicuña and guanaco fecal samples, and 22 alpaca embryos collected between 72 and 96 hours postcopula were used. The fecal and embryo samples were preserved in 96% and 70% ethanol respectively. DNA was extracted from blood and feces using commercial kits. Three methods (boiling, proteinase K and phenol-cloroform) were used to extract DNA from alpaca embryos. Two PCR techniques were developed to analyze DNA: multiplex (for fecal and blood sample DNA) and heminested PCR (for embryo cell DNA). The multiplex PCR accurately determined the sex in 100% of the DNA samples extracted from blood, in 87.5% of the samples extracted from fresh feces and in 50% of the 4-year old fecal samples. The heminested PCR, however, could not be optimized.